SOLUSI STRATEGIS ORGANISASI BISNIS MENGHADAPI PERSAINGAN DI ERA GLOBAL - Idrus, Salim Al (IQTISHODUNA, 2008)
Have been creating shift and new paradigm. The change of science and technology, economy, politic, social, value and culture, market and environment are impetus in creating thight competition. These latter condition require every company to do a transformation in its activity in order to be more efficient and competitive. The company must follow, adjust and make the use of every chance and challenge caused by the changes. The greater world’s development, the greater the need of adaptation ability. In related with economic activity, pragmatism consideration needs to be considered. It means that every company is required to obsrever world’s development comprehensively. As one of the economic power, a company must compete with other player in open and complex competition.